2018
DOI: 10.4236/nr.2018.94007
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Integrated Complementary Relationship for Estimating Evapotranspiration

Abstract: The complementary relationship for estimating evapotranspiration (ET) is a simple approach requiring only commonly available meteorological data; however, most complementary relationship models decrease in predictive power with increasing aridity. In this study, a previously developed Granger and Gray (GG) model by using Budyko framework is further improved to estimate ET under a variety of climatic conditions. This updated GG model, GG-NDVI, includes Normalized Difference Vegetation Index (NDVI), precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…We found that such NAMEs will be normally associated with much higher MAPEs by a factor of 1.7, yielding equivalent MAPEs of 27 to 107% with an average of 55%. Due to probable lack of reliability of the conventional CR models, they were later improved by adding NDVI and precipitation (Kim & Kaluarachchi, 2017, 2018), embedding surface temperature for near‐instantaneous ET simulations (Crago & Crowley, 2005), or by algorithm enhancement (Crago & Qualls, 2018). The enhancements of the algorithm, though, are not well‐established yet (Crago et al, 2020; Szilagyi & Crago, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We found that such NAMEs will be normally associated with much higher MAPEs by a factor of 1.7, yielding equivalent MAPEs of 27 to 107% with an average of 55%. Due to probable lack of reliability of the conventional CR models, they were later improved by adding NDVI and precipitation (Kim & Kaluarachchi, 2017, 2018), embedding surface temperature for near‐instantaneous ET simulations (Crago & Crowley, 2005), or by algorithm enhancement (Crago & Qualls, 2018). The enhancements of the algorithm, though, are not well‐established yet (Crago et al, 2020; Szilagyi & Crago, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple methods have been used to successfully estimate ET for agricultural areas, the heterogeneity of urban land use and cover makes it particularly difficult to estimate urban ECU using traditional ET measurement methods (Anderson & Vivoni, 2016;Grimmond & Oke, 1999;Litvak et al, 2017a;Qiu, Tan, Wang, Yu, & Yan, 2017). Given the uncertainty inherent in ET estimation methods, particularly when applying these methods to urban landscapes, using a combination of methods to estimate urban ECU can provide a more accurate overall representation of urban ECU and the identification of separate components of urban ECU (Allen, Pereira, Howell, & Jensen, 2011;Kim & Kaluarachchi, 2018;Reitz, Senay, & Sanford, 2017).…”
mentioning
confidence: 99%